The Design of A Canteen Organic Waste Management System Using Black Soldier Fly at Universitas Jambi - Mutmainnah, Elma; Jalius; Hutagalung, Winny Laura Christina (Departemen Teknik Sipil dan Lingkungan IPB, 2025)
Universitas Jambi adopted the Green Campus concept and joined the UI Green Metric as a commitment to environmental sustainability. One crucial step is the management of solid waste, particularly organic waste. In 2023, Universitas Jambi generated 835.7 kg of organic waste per day; however, its management at the Temporary Disposal Site remains suboptimal. This study aimed to measure the amount of organic waste from canteens in the Mendalo Campus area, evaluate the effectiveness of the Black Soldier Fly (BSF) method, and design a sustainable organic waste management system. The results show that the BSF method can reduce waste by up to 77.5%, with a Waste Reduction Index (WRI) of 5.16% and an Efficiency Conversion Degree (ECD) of 9.15%. BSF larvae have proven to be effective in processing various types of organic waste, making this bioconversion technique widely applicable at the Universitas Jambi. The proposed management system includes waste collection from sources, transportation, and processing using BSF to enhance the efficiency of organic waste management.